Short and long-term effects of the 1998 Bangladesh flood on rural wages - Mueller, Valerie; Quisumbing, Agnes R. (International Food Policy Research Institute, 2010)
Natural disasters have particularly devastating impacts on economic growth in developing countries because they impede the accumulation of capital. The resilience of labor markets is crucial especially for the poor who rely only on labor to diversify their income portfolio and buffer against risk. Such a risk management strategy may become more challenging as global climate change increases the frequency of natural disasters. We use the Bangladesh Flood Impact panel household survey to evaluate how the 1998 “flood of the century” affected wages in Bangladesh. We find long-term declines in wages where nonagricultural labor markets are more severely affected. We also evaluate how soil quality and proximity to auxiliary labor markets cushion labor markets against the disaster. The most compelling evidence shows that workers in areas further from centers of economic activity are more vulnerable to flood-induced wage losses. Our findings suggest that future emergency relief and climate change programs should consider the protection of labor markets by improving infrastructure to facilitate job searches in alternative locations or reduce migration costs.